Floristic Metaphor in French and Tatar Literary Texts - SHEMSHURENKO, Оksana Vladimirovna; MINGAZOVA, Raushaniya Razulovna; GUZMAN CORTEZ, Marisol (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study is devoted to the floristic units of the french and tatar language, which underwent a metaphorical transformation in artistic discourse. The aim of the study is to determine the most significant directions of metaphorical transfer, to identify the common and unique in the process of metaphorization in languages of different structure. The objects of study were floronyms - names of plants in French and Tatar languages, meronyms - names of parts of a plant, as well as lexical units indicating the stage of plant development. The results of the work can be applied in studies of lexicography, translation studies and language theory.RESUMEN Este estudio está dedicado a las unidades florísticas del idioma francés y tártaro, que sufrieron una transformación metafórica en el discurso artístico. El objetivo del estudio es determinar las direcciones más significativas de la transferencia metafórica, para identificar lo común y único en el proceso de metaforización en lenguajes de diferente estructura. Los objetos de estudio fueron florónimos: nombres de plantas en francés y tártaro, merónimos, nombres de partes de una planta, así como unidades léxicas que indican la etapa de desarrollo de la planta. Los resultados del trabajo pueden aplicarse en estudios de lexicografía, estudios de traducción y teoría del lenguaje.